2018
DOI: 10.1016/j.nmni.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis and description of an outbreak due to carbapenem-resistant Ochrobactrum anthropi causing pseudo-bacteraemias

Abstract: Ochrobactrum anthropi, a rare human pathogen, has been isolated predominantly from patients with catheter-related bacteraemia and rarely from other infections. In 2016, six cases of pseudo-bacteraemia caused by carbapenem-resistant O. anthropi isolates were recovered from an Argentinian hospital. The resistant phenotype exposed by the isolates caught our attention and led to an extensive epidemiologic investigation. Here we describe the characterization of a carbapenem-resistant O. anthropi outbreak whose prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…1; also, see Table S2). The genera Pseudomonas, Stenotrophomonas, Acinetobacter, Algoriphagus, Alteromonas, Brevundimonas, Caulobacter, Chryseobacterium, Empedobacter, Sphingomonas, Sphingopyxis, Pseudoxanthomonas, Flavobacterium, Cupriavidus, Myroides, Ochrobactrum, Pedobacter, Phenylobacterium, and Rhizobium, for which we found isolates with resistance, have already been described to have CR (5,17,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). In contrast, the genera Chromobacterium, Rheinheimera, Variovorax, Aquiflexum, Chitinophaga, Herbaspirillum, and Xanthobacter were not known to contain CR at the time of isolation.…”
Section: Resultssupporting
confidence: 58%
“…1; also, see Table S2). The genera Pseudomonas, Stenotrophomonas, Acinetobacter, Algoriphagus, Alteromonas, Brevundimonas, Caulobacter, Chryseobacterium, Empedobacter, Sphingomonas, Sphingopyxis, Pseudoxanthomonas, Flavobacterium, Cupriavidus, Myroides, Ochrobactrum, Pedobacter, Phenylobacterium, and Rhizobium, for which we found isolates with resistance, have already been described to have CR (5,17,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). In contrast, the genera Chromobacterium, Rheinheimera, Variovorax, Aquiflexum, Chitinophaga, Herbaspirillum, and Xanthobacter were not known to contain CR at the time of isolation.…”
Section: Resultssupporting
confidence: 58%
“…[ 13 ] Of note, the increased rate of females in the BLAL group, confirming a sexual dimorphism in antibiotic allergy, also suggests the effect of the genetic background. [ 14 , 15 ] A BLAL was found in only 11% of electronic medical files. This under-reporting could have participated to the low prevalence rate that we found.…”
Section: Discussionmentioning
confidence: 99%
“…This mirrors the nearly universal resistance of these antimicrobial groups reported in the literature; all isolates reviewed were also resistant to the majority of β-lactams as well as β-lactam inhibitors, thus exhibiting an AmpC-like phenotype. Regarding carbapenems, our isolates, as well as the majority of reported isolates, showed low MIC values for this group (100% and 71%, respectively), apart from a unique cluster of carbapenem-resistant isolates in a "pseudo-bacteremia" event described in a single study [20]. Resistance to aminoglycosides appeared variable, with a median MIC value for gentamicin of 4 µg/mL (range 0.256-256) in 104 reported isolates.…”
Section: Phenotypic Datamentioning
confidence: 62%
“…The antimicrobial susceptibility testing results for our five Ochrobactrum isolates are presented in Table 2. We reviewed the literature for studies describing phenotypic susceptibility patterns and found minimal inhibitory concentration (MIC) data for various antimicrobials for a total of 114 isolates [17][18][19][20]22]; the MIC ranges and medians are summarized in Table 2. All five isolates were resistant to both penicillins and cephalosporins (MICs ≥ 32µg/mL).…”
Section: Phenotypic Datamentioning
confidence: 99%